Case Report: Adult NTRK-Rearranged Spindle Cell Neoplasm: Early Tumor Shrinkage in a Case With Bone and Visceral Metastases Treated With Targeted Therapy - Recine, Federica; De Vita, Alessandro; Fausti, Valentina; Pieri, Federica; Bongiovanni, Alberto; Franchini, Eugenia; Casadei, Roberto; Falasconi, Maria Cristina; Oboldi, Devil; Matteucci, Federica; Pallotti, Maria Caterina; Mercatali, Laura; et al. (Frontiers in Oncology, 2022)
Background: NTRK (neurotrophic tyrosine receptor kinase)-rearranged spindle cell neoplasms are a new group of tumors included in the new 5th edition of the World Health Organization (WHO) classification of soft Tissue and Bone Sarcomas. These tumors are characterized by NTRK gene fusions and show a wide spectrum of histologies and clinical behavior. Several targeted therapies have recently been approved for tumors harboring NTRK fusions, including STS. Case presentation: A 26-year-old male with advanced, pretreated NTRK rearranged spindle cell neoplasm and liver, lung and bone metastases was treated with larotrectinib on a continuous 28-day schedule, at a dose of 100 mg twice daily. An 18FDG-PET/CT scan performed after 7 days of treatment showed tumor shrinkage in both visceral and bone lesions. There was no drug-related toxicity. Subsequent evaluations confirmed continued tumor regression in disease sites. The patient is well and continues treatment. Conclusion: The clinical and radiological response of our patient with an uncommon TPM4 (exon 7)-NTRK1 (exon 12) gene fusion tumor treated with a first-generation TRK inhibitor could contribute to a better understanding of the biology of this new STS entity and help to improve patient management.